Proceedings of 2005 International Conference on Intelligent Sensing and Information Processing, 2005.
DOI: 10.1109/icisip.2005.1529482
|View full text |Cite
|
Sign up to set email alerts
|

Combining evidence from multiple classifiers for recognition of consonant-vowel units of speech in multiple languages

Abstract: ApstractIn this paper, we present studies on combining evidence from multiple classifiers to recognize a large number of consonant-vowel (CV) unit.s of speech. Multiple classi fier systems may lead to a better solution to the complex speech recognition tasks, when the evidence obtained from individual systems is complementary in nature.Hidden Markov models (HIvlMs) are based on the max imum likelihood (ML) approach for training CV pat terns of variable lengt.h. Support vector machine (SVM) models are based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 2 publications
0
27
0
Order By: Relevance
“…In [15] they acknowledge the fact that the classification error patterns from SVM and HMM classifiers may be different and thus their combination could result in a gain in performance. They assess this statement on a classification task of consonant-vowel units of speech in several Indian languages obtaining a marginal gain by using a sum rule combination scheme of the two classifiers' evidences.…”
Section: Non-uniform Feature Sequence Resamplingmentioning
confidence: 99%
“…In [15] they acknowledge the fact that the classification error patterns from SVM and HMM classifiers may be different and thus their combination could result in a gain in performance. They assess this statement on a classification task of consonant-vowel units of speech in several Indian languages obtaining a marginal gain by using a sum rule combination scheme of the two classifiers' evidences.…”
Section: Non-uniform Feature Sequence Resamplingmentioning
confidence: 99%
“…This problem has been overcome by state clustering in models [11]. Recent studies have shown that syllables (combinations of phones) are also promising subword units for speech recognition [3,4,8,19,21]. Context-dependent units such as syllables capture significant co-articulation effects and pronunciation variations compared to phones.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the syllable-like units are of type C m V C n , where C refers to a consonant, V refers to a vowel, and m and n refer to the number of consonants preceding and following the vowel, respectively. Among these units, the consonant vowel (CV) units are the most frequently (around 90% in Indian languages) occurring units [4]. Hence CV units are considered for our studies in this work.…”
Section: Introductionmentioning
confidence: 99%
“…Some of them perform a previous processing of the speech or feature sequence in order to obtain fixed dimension vectors that fit the SVM input. This normalization can be achieved by means of simple uniform [35] or non-uniform [36], [37] feature sequence resampling procedures. Other authors apply the socalled triphone model approach, which assumes that speech segments corresponding to phones are composed of a fixed number of sections (3 in most cases).…”
Section: Hybrid Svm/hmm Systemsmentioning
confidence: 99%